2015
DOI: 10.1080/10919392.2015.1033935
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Antecedents and Consequences of Live Chat Use in Electronic Markets

Abstract: Online shopping has progressed from having consumers passively browse through the webpages of online stores to having them proactively engage in communication dialogues with the sellers themselves via live chat. Modern-day consumers can now directly contact online sellers and inquire about the products they intend to purchase through the live chat medium available in the webpages of online stores, such as Taobao.com. In this study, the conceptual framework of motivation, opportunity, and ability was extended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 60 publications
0
28
0
4
Order By: Relevance
“…Therefore, it is more relevant to study to what extent the use of chat service strengthens the relationship between two-way communication and its consequences. While previous research has found that the use of chat service is indirectly linked to positive outcomes through higher levels of interactivity (e.g., Kang et al, 2015;Ou et al, 2014;Song & Zinkhan, 2008), this study proposes that the use of chat service acts as a moderator between two-way communication and trust, satisfaction, and repurchase intention. Accordingly, the following hypotheses are formulated:…”
Section: Two-way Communicationmentioning
confidence: 66%
See 4 more Smart Citations
“…Therefore, it is more relevant to study to what extent the use of chat service strengthens the relationship between two-way communication and its consequences. While previous research has found that the use of chat service is indirectly linked to positive outcomes through higher levels of interactivity (e.g., Kang et al, 2015;Ou et al, 2014;Song & Zinkhan, 2008), this study proposes that the use of chat service acts as a moderator between two-way communication and trust, satisfaction, and repurchase intention. Accordingly, the following hypotheses are formulated:…”
Section: Two-way Communicationmentioning
confidence: 66%
“…In line with this evidence, Ou et al (2014) find that the use of an instant messenger (similar to live chat) at an e-commerce store leads to positive consumer perceptions and behaviors (e.g., trust and repurchase intention) through consumers' interactivity perceptions. Kang et al (2015) find that the use of chat service increases the perceived interactivity of an e-commerce website, which is further linked to purchase intention. In sum, there is evidence that the use of chat service has positive impacts on two-way communication, which is linked to consumer attitudes.…”
Section: Two-way Communicationmentioning
confidence: 89%
See 3 more Smart Citations